A Juxta Jotum Naturare Society or incomplete corporatism? - Jessie Jane Vieira de Sousa; Eoin Paul O'Neill (Topoi)
This work analyses in a comparative perspective, the differences between catholic corporativism and state corporative experiences that marked the world scenario throughout the period of the two world wars, particularly in Portugal, Spain, and Italy. To realize this investigation a specific area of interest is defined in an attempt not to allow that the catholic corporativism be misinterpreted as state corporativism, although both of them have a strong discipline appeal. The conservative side assumed this appeal during the emergency of the social problem as a matter of work. It is of paramount importance to understand how the catholic corporativism was displayed in Brazil and which were its connections and divergences with the catholic corporativism present in Europe at the same time. It is necessary yet, to understand the discoursive routes through which the Church built a totalitarian speech.